Developing Reflective Practice in the Early Years - Paige-Smith, Alice; Craft, Anna (Maidenhead, Berkshire, England : Open University Press, 2011)
Reflective practice is a vital aspect of working with youngsters and enables a deeper understanding of their learning and development. This book supports early years practitioners in articulating their own practice in greater depth, exploring some ways in which they can be encouraged to engage in reflecting on their practice.
Previous edition: 2007.
Includes bibliographical references and index.
Keywords: Reflective teaching; Preschool teaching; Elementary school teaching; Education